PENERAPAN AKAD MUDHARABAH MUQAYYADAH PADA BANK SYARIAH DI INDONESIA - Wahyu Syarvina (Universitas Islam Negeri Sumatera Utara, 2021)
Mudharabah Muqayyadah is a form of cooperation between shahibul mal and mudharib, where mudharib is limited by limitations on the type of business, time or place of business. Fatwa of the National Sharia Council (DSN) on the method of income smoothing of third party funds DSN Fatwa No. 87 / DSN-MUI / XII / 2012 states that in the case of a Mudharabah Muqayyadah contract, a reserve fund (PER) may also be formed through an allowance for the benefit of a customer's right that exceeds the rate of return projected after being shared with the DPK customer's permission. In this contract shahibul mal and mudarib are asked to trust each other, where shahibul mal does not receive guarantees from mudharib and mudarib to run a business in accordance with the terms and conditions of shahibul mal. The risk that the bank avoids is the risk of problematic financing, there is a sense of concern that mudarib will take the money away. Especially because mudarib does not need to provide guarantees in this case, the losses borne by the bank are getting bigger. In the Mudharabah Muqayyadah contract, the bank finds it difficult to implement it based on the shahibul mall not only one person and each customer has different desires, terms and opinions.